Inheritance Tax Evasion in Germany - Linseis, Philippe (Journal of Legal Studies, 2022)
It is estimated, that between 2015 and 2024 about 3 trillion € will be inherited in Germany. Due to far-reaching tax exemptions, the inheritance tax revenue per year is only about 7 billion €. Despite the fact, that the income or value-added tax burden is significantly higher, the inheritance tax is more unpopular than other taxes. The objective of the paper is to figure out, whether there is evidence of high tax evasion in the field of German inheritance tax, with a view to the low tax revenue and the high unpopularity of the tax. Therefore, data from the official inheritance tax statistic is compared with secondary data from studies, which estimate the yearly wealth transfer to the next generation by using survey data. The assumption is, that asset classes, which are easy to evade, should be recorded with a lower amount in the official tax statistic, than in the survey-based estimations. But the results do not show evidence of high tax evasion in the field of inheritance tax. As until now, only a small part of the inheritances is recorded in the official inheritance tax statistic, for the future it is recommended to the government, to record all inheritances in the official statistic. Because of far-reaching reporting obligations, the tax offices anyway have knowledge of most inheritances and the additional bureaucratic effort to record the additional data in the official tax statistic is small.